Delayed manifestation of bilateral scleral thinning after I-BRITE® procedure and review of literature for cosmetic eye-whitening procedures - Moshirfar M (Dove Medical Press, 2015)
Majid Moshirfar,1 Michael V McCaughey,2 Carlton R Fenzl,3 Luis Santiago-Caban,4 Gregory D Kramer,3 Nick Mamalis3 1Department of Ophthalmology, Francis I Proctor Foundation, University of California San Francisco, San Francisco, CA, USA; 2University of New Mexico School of Medicine, Albuquerque, NM, USA; 3John A Moran Eye Center, University of Utah, Salt Lake City, UT, USA; 4Department of Ophthalmology, University of Puerto Rico School of Medicine, San Juan, PR, USA Purpose: To report a case of delayed-onset bilateral scleral thinning and calcium deposition following a cosmetic ocular-whitening procedure (I-BRITE®).Methods: A 33-year-old male patient with a history of right-sided ptosis repair and left-sided anterior uveitis had previously undergone bilateral I-BRITE treatment for chronic conjunctival hyperemia. Four years after the procedure, the patient was referred to our institution with bilateral scleral thinning and overlying calcific depositions. A literature review was performed through PubMed from 1980 through 2014 using the search terms ‘cosmetic’, ‘ocular’, ‘conjunctivectomy’, ‘regional conjunctivectomy’, ‘I-BRITE’, ‘eye-whitening’, ‘scleritis’, ‘necrotizing scleritis’, ‘anterior uveitis’, ‘mitomycin C’, ‘5-fluorouracil’, and ‘bevacizumab’, along with associated cross-referencing from relevant articles.Results: Examination of the patient revealed bilateral necrotizing scleritis within the nasal region of both eyes. Calcified plaques were also present within the areas of scleromalacia, along with epithelial defects demonstrated with fluorescein staining. Although evidence of previous intraocular inflammation was apparent within the left eye, there were no active signs of inflammation evident within either eye on initial presentation. Complication rates reported in the literature include: scleral thinning (1.8%), calcific plaque formation (2.9%), fibrovascular proliferation (13%), diplopia (1.2%), elevation of intraocular pressure (4.2%), and recurrence of conjunctival hyperemia (2.1%).Conclusion: Cosmetic ocular whitening procedures have an attendant high complication rate, and have been associated with several adverse postoperative complications, which have in turn generated several reservations regarding the veritable benefit of the procedure. Many postsurgical complications may demonstrate delayed apparition, varying from several months to several years after primary surgical intervention as in the case reported here. Keywords: necrotizing scleritis, scleromalacia, cosmetic ocular whitening